Biofilm production and antibiotic susceptibility of Staphylococcus epidermidis strains from Hidradenitis Suppurativa lesions. (7th August 2018) - Ardon, C.B.; Prens, E.P.; Fuursted, K.; Ejaz, R.N.; Shailes, J.; Jenssen, H.; Jemec, G.B.E.
Abstract: Background: An aberrant interaction between commensal skin bacteria and the host skin immune system is considered important in the pathogenesis of hidradenitis suppurativa (HS). Objective: In this study, we investigated the antibiotic susceptibility and biofilm‐forming capabilities of S. epidermidis strains isolated from HS patients. Methods: Skin biopsies were taken from active HS lesions such as inflammatory nodules and/or sinuses and non‐involved skin from 26 patients and cultured under optimal microbiological conditions for 24 h. Planktonic growth, biofilm production, antibiotic susceptibility and biofilm eradication by clindamycin, doxycycline, rifampicin and tetracycline were tested including a laboratory control strain of S. epidermidis for reference. Results: Staphylococcus epidermidis was cultured in 16 of 26 HS patients (62%). In total 27 different S. epidermidis isolates were identified; 16 (59%) from non‐involved skin and 11 (41%) from HS lesions. All bacterial strains showed planktonic growth. Twenty‐four of 27 (89%) isolates were strong biofilm producers in vitro . The biofilm‐forming capability varied amongst the strains from non‐involved skin and lesional skin. Twenty‐four strains had an intermediate to resistant antibiotic susceptibility to clindamycin (89%). Rifampicin was the most effective antibiotic at inhibiting planktonic growth and at eradication of biofilm ( P < 0.05). Conclusion: We observed a slight increase in S. epidermidis virulence, characterized by resistance to commonly used antibiotics, increased biofilm production and resistance to biofilm eradication. In particular, the reduced sensitivity to tetracycline and clindamycin, two standard antibiotics in the treatment of HS, is alarming. Rifampicin, also important in HS treatment, showed the greatest efficacy at eradicating the biofilm at low MIC concentrations.